Studi Metode Spektroskopi Plasma Laser Tekanan Rendah untuk Identifikasi Unsur Tembaga - Ainul Ibnu Khotob; Wahyu Setia Budi; Ali Khumaeni (Youngster Physics Journal, 2016)
The study on laser plasma spectroscopy has been conducted in Optoelectronics and Laser Laboratory, Physics Department, Diponegoro University, to identify the copper spectrums in samples of pure copper and copper alloys. In this study, some of the tested parameters are the comparison of ambient pressure, laser energy and types of sample. In comparative study on ambient pressure, the researcher compared the plasma laser and the spectrum that is constructed of pure copper at the pressure of 1 atm and 3 Torr with PFN 85%. The study on varieties of laser energy was conducted with the PFN values used on pure copper sampel which is at 3 Torr condition, between the range of 75%, 80%, 85%, 90% and 95%. In the test on sample types, the samples used are pure copper, commercial copper, brass key (Cu-Zn) and bronze coin (Cu-Al), at the pressur of 3 Torr and PFN 85%.. As the result, the plasma on ambient pressure of 3 Torr were formed bigger than at 1 atm and it has more clear and better colored spectrum. The higher value of laser’s PFN also lead to greater formed plasma. The dominant and consistent spectrums formed are Cu I 521,82 nm, Cu I 515,32 nm, Cu I 510,56 nm and Cu I 406,26 nm. Based on the calculation conducted by using the Boltzmann plot method, the value f plasma’s temperature that has been formed is rangen in value of 9503,37 – 10906,54 Kelvin.